Nanomedicine mediated thyroid cancer diagnosis and treatment: an approach from generalized to personalized medicine - Deepak Gulwani; Priyanka Upadhyay; Ridhima Goel; Vijaya Sarangthem; Thoudam Debraj Singh (Discover Oncology)
Abstract Thyroid cancer (TC) being the common endocrine malignancy is glooming steadily due to its poor prognosis. The treatment strategies of surgery, radiotherapy, and conventional chemotherapy are providing unsatisfactory output. However, combination therapy can negotiate the worse prognosis to the better, where chemoradiotherapy, radiotherapy with surgery, or dual chemotherapeutic drugs are being glorified. Chemotherapy includes the use of doxorubicin or taxanes generally with platinum-based drugs viz. cisplatin or carboplatin that are administered alone or along with multitarget tyrosine kinase inhibitors viz. Lenvatinib, Sorafenib, Sunitinib, Vandetanib, Pyrazolo-pyrimidine compounds, etc., single target tyrosine kinase inhibitors like Dabrafenib plus Trametinib and Vemurafenib against BRAF, Gefitinib against EGFR, Everolimus against mTOR, vascular disruptors like Fosbretabulin, and immunotherapy with viz. Spartalizumab and Pembrolizumab, are anti-PD-1/PD-L1 molecules. Hence, several trials are currently evaluating the possible beneficial role of combinatorial therapy in TC. Since TC is the outcome of multiple genetic alterations, it necessitates targeting the multiple factors in a single shot. These combination strategies for systemically delivering therapeutic drugs seem feasible only with the help of theranostic. To date, nanoparticle-based drug delivery systems (NDDS) have devoted themselves to diagnosis, bioimaging, imaging-assisted surgery, and therapy with high success rates. The ease of handling hybrid technologies is also selectively admirable. However, in this review, we have summarized the sequential progression of chemotherapeutic drugs to NDDS designed for Personalized Medicine (PM) against TC. Personalized medicine is an ever-growing field that will be explored in future discoveries in biomedicine, particularly cancer theranostics. Hence, our review presents a closer view of NDDS as a personalized treatment for TC. We have also discussed the primary challenges facing NDDS in meeting excellence in PM.